2013
DOI: 10.1007/s10900-013-9724-7
|View full text |Cite
|
Sign up to set email alerts
|

Performance Assessment Through Pre- and Post-training Evaluation of Continuing Medical Education Courses in Prevention and Management of Cardio-Vascular Diseases in Primary Health Care Facilities of Armenia

Abstract: To assess the difference of pre- and post-training performance evaluation of continuing medical education (CME) courses in cardio-vascular diseases (CVD) management among physicians at primary health care facilities of Armenian regions we conducted an evaluation survey. 212 medical records were surveyed on assessment of performance before and after the training courses through a self-employed structured questionnaire. Analysis of survey revealed statistically significant differences (p < 0.05) in a number of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Participants noted improved trust and knowledge among primary care and secondary care physicians, according to the reflexive methods implemented in the joint training meetings, which are factors that influence care coordination by promoting the interest of professionals in collaborating and communicating with others levels of care [ 2 51 ]. Therefore, it is important to spread this type of intervention in order to improve clinical coordination by promoting agreement on treatments and establishing joint reference criteria, resulting in more appropriate and timely referrals [ 52 53 ], which occurred during the joint training meetings on maternal health, compared to conventional training [ 54 55 56 57 ]. This aspect is especially relevant for the Veracruz context, in which the results of the baseline study showed low values for mutual trust (11.5%) and personal knowledge (49.9%) among physicians in the healthcare network [ 3 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants noted improved trust and knowledge among primary care and secondary care physicians, according to the reflexive methods implemented in the joint training meetings, which are factors that influence care coordination by promoting the interest of professionals in collaborating and communicating with others levels of care [ 2 51 ]. Therefore, it is important to spread this type of intervention in order to improve clinical coordination by promoting agreement on treatments and establishing joint reference criteria, resulting in more appropriate and timely referrals [ 52 53 ], which occurred during the joint training meetings on maternal health, compared to conventional training [ 54 55 56 57 ]. This aspect is especially relevant for the Veracruz context, in which the results of the baseline study showed low values for mutual trust (11.5%) and personal knowledge (49.9%) among physicians in the healthcare network [ 3 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coexistence of specialists in PHC facilities does not motivate family doctors to learn more, because it is easier to refer them to specialists (Asadov and Aripov, 2009;Oleszczyk et al, 2012). Therefore, it is important to prepare health professionals for PHC with a focus on prevention and early detection of diseases at undergraduate, postgraduate, and continuous medical education levels (Lilit Khachatryan, 2013;Krzton-Krolewiecka et al, 2013;Gruzeva et al, 2016aGruzeva et al, , 2016b. A study conducted in 30 European countries and some CIS countries confirmed that building General Practice/Family Medicine in academic discipline comprising teaching and research was essential to strengthen the PHC system (Zarbailov et al, 2017;Kasimova, 2018;Akhmedov and Jarylkasynova, 2010).…”
Section: Health Workforcementioning
confidence: 99%
“…The vast majority of Armenian citizens believe that the diaspora is a positive force in the development of the country [ 8 ]. The Armenian diaspora has made numerous healthcare contributions to the country: Short-term mission trips to various villages, conferences between diaspora and local healthcare professionals, collaborations with local physicians on conducting research and organizing continuing medical education courses [ 15 ]. However, these efforts tend to focus on short-term interventions, they are largely uncoordinated, and their impact is rarely measured.…”
Section: Welcoming Diaspora Involvementmentioning
confidence: 99%